Peran Komunikasi Pembangunan Dialogis Terhadap Pemanfaatan Hasil Pembangunan Yang Belum Merata Untuk Tujuan Pembangunan Berkelanjutan - Ardiana, Oktavia Dwi; Azzahra, Dinda; Sachmaso, Hana Humaira; Harsanti, Khairunnisa Putri; Salsabila, Syana Mifta (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The equitable development of infrastructure is a crucial aspect for achieving the Sustainable Development Goals (SDGs). However, in certain regions such as Lampung, inequalities still exist in the utilization of infrastructure development outcomes. This article aims to analyze the role of dialogic development communication in maximizing the utilization of uneven infrastructure development in Lampung, as well as how the implementation of these development outcomes can support the achievement of sustainable development. Using a literature review method, the article explores two key questions: how the role of dialogic communication ensures the participation of local communities and governments in the utilization of infrastructure, and how the existing infrastructure in Lampung can be more evenly implemented to support SDG achievement. Based on the analysis, dialogic communication serves as a medium that enables the exchange of information and ideas among stakeholders, thereby enhancing community involvement in decision-making related to infrastructure use. Furthermore, participatory implementation is considered a key step in addressing development inequality, strengthening social inclusion, and optimizing the benefits of development for all societal groups.